WEBSITE USABILITY TESTING ON THE INFORMATION AND COORDINATION CENTER OF COVID-19 IN WEST JAVA USING THE SYSTEM USABILITY SCALE - Dwi Andini Putri; Denda Rinaldi Hadinata; Siti Nurwahyuni (LPPM Nusa Mandiri, 2020)
Indonesia is one of the countries affected by the COVID-19 outbreak. Positive confirmed patients in Indonesia are increasing every day. The people became restless and worried because of this outbreak. Website becomes one of the media used in conveying information on the spread of COVID-19. However, the website has several weaknesses in its use such as, appearance that is too complicated, writing that is not clearly readable, there is no data update in real time, and unusual menu choices. The official website established by the West Java government in tackling the spread of COVID-19 is pikobar.jabarprov.go.id or known as The Information and Coordination Center of COVID-19 website in West Java Province (PIKOBAR). To minimize the weaknesses and the level of website usability that occurs, the PIKOBAR website needs evaluation and update. The evaluation carried out aims to make the website run well, so that it can provide up-to-date and real-time information to the public. In this study the evaluation of the PIKOBAR website is done by measuring and testing the appearance of usability using the System Usability Scale (SUS) instrument. The results showed that the SUS score obtained was 70.7 which was included in the acceptable, grade C and good categories. This means that the PIKOBAR website has good usability value and is feasible to be accessed and accepted by Users (Visitors).